Genetic structure, spatial organization, and dispersal in two populations of bat‐eared foxes. Issue 9 (26th July 2013) - Kamler, Jan F.; Gray, Melissa M.; Oh, Annie; Macdonald, David W.
Abstract: We incorporated radio‐telemetry data with genetic analysis of bat‐eared foxes ( Otocyon megalotis ) from individuals in 32 different groups to examine relatedness and spatial organization in two populations in South Africa that differed in density, home‐range sizes, and group sizes. Kin clustering occurred only for female dyads in the high‐density population. Relatedness was negatively correlated with distance only for female dyads in the high‐density population, and for male and mixed‐sex dyads in the low‐density population. Home‐range overlap of neighboring female dyads was significantly greater in the high compared to low‐density population, whereas overlap within other dyads was similar between populations. Amount of home‐range overlap between neighbors was positively correlated with genetic relatedness for all dyad‐site combinations, except for female and male dyads in the low‐density population. Foxes from all age and sex classes dispersed, although females (mostly adults) dispersed farther than males. Yearlings dispersed later in the high‐density population, and overall exhibited a male‐biased dispersal pattern. Our results indicated that genetic structure within populations of bat‐eared foxes was sex‐biased, and was interrelated to density and group sizes, as well as sex‐biases in philopatry and dispersal distances. We conclude that a combination of male‐biased dispersal rates, adult dispersals, and sex‐biased dispersal distances likely helped to facilitate inbreeding avoidance in this evolutionarily unique species of Canidae. Abstract : We incorporated radio‐telemetry data with genetic analysis of bat‐eared foxes ( Otocyon megalotis ) from individuals in 32 different groups to examine relatedness and spatial organization in two populations in South Africa that differed in density, home‐range sizes, and group sizes. Our results indicated that genetic structure within populations of bat‐eared foxes was gender biased, and was interrelated to density and group sizes, as well as sex‐biases in philopatry and dispersal distances. We conclude that a combination of male‐biased dispersal rates, adult dispersals, and sex‐biased dispersal distances likely helped to facilitate inbreeding avoidance in this evolutionarily unique species of Candiae.